CORPORATE GOVERNANCE AND DIVIDEND PAYOUTS IN NIGERIA (2015)
Corporate governance (CG) safeguards shareholders’ portfolios and ensures optimal returns in terms of dividend payouts (DPs) on investment. The association between CG and DPs could be significant in relation to risk exposure, operational and financing activities across firms and sectors. Also, the differential dividend payment between large and small firms might be due to economies of scale enjoyed by large firms. The relationship between CG and DPs has been well researched, however; the role of firm size and sectoral classification on these two has not been given adequate consideration in the literature. This study, therefore, examined the moderating effects of firm size and sectoral classification of CG on DPs in Nigeria. Agency theory provided the basis for the articulation of the model which captured the effects of CG on DPs. Governance indicators (number of independent directors, institutional investors, board size and managerial shareholding) and dividend per share of 101 non-financial listed companies in Nigeria from 1995-2012 were compiled from annual reports and statements of accounts of the firms; as well as various issues of the Nigerian Stock Exchange Factbook. The analysis was conducted at aggregate, size and sectoral levels. The firms were categorised into small (38) and large (63) based on their total assets. A sample was taken from agriculture (6), automobile (6), building (8), brewery (6), chemical/paints (9), conglomerates (9), construction (6), food and beverages, (17), healthcare (11), industrial/domestic products (10), petroleum (9) and printing/publishing (4) sub-sectors. The system generalised method of moments estimation technique that included both level and difference equations was employed. It accommodates firm level characteristics and addresses autocorrelation bias. Diagnostic tests were carried out to ascertain the robustness of the parameter estimates. All the estimates were validated at p = 0.05. A one percent increase in the number of independent directors and shareholding of institutional investors generated 68.0% and 0.9% increase in DPs respectively. The DPs rose by 10.7%, 8.0% and 0.05% given a percentage increase in profits after tax, gross earnings and previous dividend, respectively. Conversely, DPs declined by a 23.0% with a one percent increase in managerial shareholding. The relationship between CG and DPs was positive in large firms and negative in small firms. This relationship was positive in only conglomerate (18.3%), building materials (5.01%), petroleum and marketing (3.8%), brewery (2.9%), food and beverages (1.09%) and automobile and tyre (0.22%) sub-sectors respectively, while it is negative in healthcare (-0.04%), industrial and domestic products (-0.11%), chemical and paints (-0.11%), printing and publishing (-0.5%), construction (-2.8%) and agriculture (-7.01%) sub-sectors respectively. Corporate governance influence on dividend payouts differed by size of firm and sectors of operation. More independent directors should be on the boards of corporate firms and the proportion of institutional shareholding should also be increased to improve monitoring.